Synthesis and Characterization of SiO2 Nanoparticles and Their Efficacy in Chemical Mechanical Polishing Steel Substrate - M. J. Kao; F. C. Hsu; D. X. Peng (Advances in Materials Science and Engineering)
Chemical mechanical polishing (CMP) technology is extensively used in the global planarization of highly value-added and large components in the aerospace industry. A nanopowder of SiO2 was prepared by the sol-gel method and was compounded into polishing slurry for the CMP of steel substrate. The size of the SiO2 abrasives was controlled by varying the sol-gel reaction conditions. The polishing efficacy of nano-SiO2 was studied, and the CMP mechanism with nanosized abrasives was further investigated. The proposed methods can produce SiO2 abrasives whose size can be controlled by varying the sol-gel reaction conditions. The size of the SiO2 abrasives was controlled in the range from 58 to 684 nm. The roughness of the steel substrate strongly depends on the size of the abrasive, and the surface roughness decreases as the abrasive size declines. A super-smooth surface with a roughness of 8.4 nm is obtained with nanosized SiO2. Ideal CMP slurry can be used to produce material surfaces with low roughness, excellent global planarization, high selectivity, an excellent finish, and a low-defected rate.